Renewable Musa Sapientum derived porous nano spheres for efficient energy storage devices - Vandana Molahalli; Gowri Soman; Vinay S Bhat; Jyothi M S; Uraiwan Sirimahachai; Sanjeev Maradur; Paola De Padova; Nattaporn Chattham; Gurumurthy Hegde (Nano Express, 2024)
Biomass-based carbonaceous materials derived from Musa Sapientum have gained much attention in recent years for their application in energy storage devices, especially supercapacitors. In the present work, we synthesized carbonaceous material from banana peel as the biomass precursor by using a pyrolysis method carried out at various temperatures (600, 800, and 1000 °C). The characterization of the prepared carbonaceous materials BP600, BP800 and BP1000 was done by using different characterization techniques such as FTIR, XRD, FE-SEM, and TEM, studies. The electrochemical study of the synthesized material was carried out by cyclic voltammetry (CV), galvanostatic charge–discharge (GCD) electrochemical impedance spectroscopy (EIS). The supercapacitive performance of the material was studied using a 3-electrode system with 3M KOH as an electrolyte. As a result, the BP600 exhibited a better specific capacitance with higher energy and power densities along with a maximum cyclic stability of 16,000 cycles. To show the practical applicability of the material BP 600, two electrode system studies were carried out as well, which showed preferentially good values for specific capacitance with appreciable power and energy density values. The study provides us with a green approach for the fabrication of non-toxic, low-cost, and environmentally friendly potential porous carbonaceous electrode materials by converting bio-waste into a clean and renewable source of energy.